Mesenchymal stem cells exhibit resistance to topoisomerase inhibition. Issue 1 (28th April 2016) - Nicolay, Nils H.; Rühle, Alexander; Perez, Ramon Lopez; Trinh, Thuy; Sisombath, Sonevisay; Weber, Klaus-Josef; Schmezer, Peter; Ho, Anthony D.; Debus, Jürgen; Saffrich, Rainer; Huber, Peter E.
Highlights: Bone marrow suppression is commonly the dose-limiting toxicity of topoisomerase-inhibiting anticancer drugs. Mesenchymal stem cells are resistant to topoisomerase inhibition and maintain their defining functional stem cell properties. Mesenchymal stem cells efficiently repair DNA damage induced by topoisomerase I and II inhibitors. Mesenchymal stem cell infusions may be investigated as a therapy for topoisomerase inhibitor-induced bone marrow damage. Abstract: Background: Inhibition of cellular topoisomerases has been established as an effective way of treating certain cancers, albeit with often high levels of toxicity to the bone marrow. While the involvement of mesenchymal stem cells (MSCs) in bone marrow homeostasis and regeneration has been well established, the effects of topoisomerase-inhibiting anticancer agents remain largely unknown. Materials and Methods: Human bone marrow MSCs were treated with topoisomerase I inhibitor irinotecan or topoisomerase II inhibitor etoposide, and survival and apoptosis levels were measured. The influence of topoisomerase inhibition on cellular morphology, adhesion and migration potential and the ability to differentiate was assessed. Additionally, the role of individual DNA double-strand break repair pathways in MSCs was investigated as a potential cellular mechanism of resistance to topoisomerase inhibitors. Results: Human bone marrow MSCs were found relatively resistant to topoisomerase I and II inhibitors and show survival levels comparable to these of differentiated fibroblasts. Treatment with irinotecan or etoposide did not significantly influence cellular adhesion, migratory ability, surface marker expression or induction of apoptosis in human MSCs. The ability to differentiate was found preserved in MSCs after exposure to high doses of irinotecan or etoposide. MSCs were able to efficiently repair DNA double-strand breaks induced by topoisomerase inhibitors both by non-homologous end joining and homologous recombination pathways. Conclusion: Our data demonstrate a topoisomerase-resistant phenotype of human MSCs that may at least in part be due to the stem cells' ability to efficiently remove DNA damage caused by these anticancer agents. The observed resistance of MSCs warrants further investigation of these cells as a potential therapeutic option for treating topoisomerase inhibitor-induced bone marrow damage.